From biological marker to clinical application: the role of anti-Müllerian hormone for delayed puberty and idiopathic non-obstructive azoospermia in males - Yuanyuan Zeng; Guicheng Zhao; Yi Zheng; Xiaohui Jiang (Endocrine Connections)
Anti-Müllerian hormone (AMH), a biomarker secreted by Sertoli cells in the testes, has emerged as a critical indicator of male reproductive function with significant clinical application potential. AMH reflects Sertoli cell activity and plays a pivotal role across different stages of male gonadal function. First, in prepubertal males, AMH levels are crucial for assessing testicular development and the progression of puberty, with delayed or insufficient AMH secretion often being associated with disorders such as delayed puberty. Second, in reproductive-age males, AMH serves as an important biomarker for evaluating spermatogenic capacity, particularly in cases of idiopathic non-obstructive azoospermia. In these patients, AMH levels can help predict the success of testicular sperm extraction, thereby influencing fertility treatment strategies. This review explores the physiological mechanisms of AMH and its diagnostic and prognostic significance in both delayed puberty and fertility disorders in reproductive-age males. While AMH shows great promise in the management of hypogonadism, further research is needed to validate its clinical utility and refine treatment protocols for optimizing patient outcomes.